2019
DOI: 10.1007/s00330-019-06488-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MRI and auto-fixed volume of interest-based radiomics signature for clinically significant peripheral zone prostate cancer

Abstract: Objectives To create a radiomics approach based on multiparametric magnetic resonance imaging (mpMRI) features extracted from an auto-fixed volume of interest (VOI) that quantifies the phenotype of clinically significant (CS) peripheral zone (PZ) prostate cancer (PCa). Methods This study included 206 patients with 262 prospectively called mpMRI prostate imaging reporting and data system 3-5 PZ lesions. Gleason scores > 6 were defined as CS PCa. Features were extracted with an auto-fixed 12-mm spherical VOI pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 51 publications
5
61
1
1
Order By: Relevance
“…Monti et al [24] found that for PCa detection, standard radiomics models using T2w and ADC images performed better than an advanced model with additional diffusion kurtosis imaging and DCE. Approaches extracting radiomic features from prostate mpMRI using auto-fixed VOIs have also achieved promising results on peripheral zone csPCa detection, with the highest AUC of 0.87 for the XGBoost classifier [19]. On the other hand, Bonekamp et al [20] showed that for PCa detection, mADC alone achieved good results, comparable to clinical interpretation, and found no further benefit with complex radiomics and machine learning methods, which is in line with our study results.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Monti et al [24] found that for PCa detection, standard radiomics models using T2w and ADC images performed better than an advanced model with additional diffusion kurtosis imaging and DCE. Approaches extracting radiomic features from prostate mpMRI using auto-fixed VOIs have also achieved promising results on peripheral zone csPCa detection, with the highest AUC of 0.87 for the XGBoost classifier [19]. On the other hand, Bonekamp et al [20] showed that for PCa detection, mADC alone achieved good results, comparable to clinical interpretation, and found no further benefit with complex radiomics and machine learning methods, which is in line with our study results.…”
Section: Discussionsupporting
confidence: 89%
“…In the small lesion subgroup, PI-RADS was non-inferior to our model, which suggests that radiologist reassessment could measurably improve the predictions. Previous studies commonly excluded lesions with volumes of less than 0.5 ml from their analysis [ 19 , 26 , 29 , 30 , 31 , 32 ] or provided no information about the distribution of lesion volumes [ 20 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The classification method has a strong impact on the variation in performance [19]. Yet, the question has not been addressed to what extend specific feature and prediction model effect the diagnostic performance to differentiate GrG ≤ 2 against GrG ≥ 3 [3,[22][23][24][25][26]. The purpose of this study was to evaluate the application of the clinical assessment categories PI-RADS and ADCderived radiomic features to build and compare three prediction models and to analyze their influence on the differentiation of clinically significant PCa.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have utilized a standard pipeline for radiomic analysis, including the following main steps: image acquisition, segmentation (or labeling), feature extraction, feature selection, and statistical and predictive modeling [ 41 , 78 , 79 , 80 , 81 ]. Figure 1 illustrates the process of radiomic analysis as it pertains to identifying signatures for establishing the PCa grade group, as previously implemented by Chaddad et al [ 23 , 24 ].…”
Section: Radiomics Pipeline For Predicting Tumor Gradementioning
confidence: 99%